Estrutura da testa de Leguminosae e sua influência na aquisição de dormência física pré e pós-dispersão - Camila Ribeiro Magalhães (2021)
The seed coat externally covers the seed, and its primary function is to protect the embryo. In mature seed, testa, and tegmen, if differentiated, can prevent germination if there is impermeability. Impermeable seed coats promote physical dormancy, which is usually related to one or more layers of palisade cells that often occur in the testa and to hydrophobic substances embedded in the walls of these cells. Among Leguminosae species, physical dormancy is very common. An important aspect to investigate is the structural since, despite being well known, there are still gaps in the structural characterization of the typical testa of Leguminosae in several works. Another interesting element is the environment’s influence, maternal and storage, on the acquisition of physical dormancy among legumes. It is known that environmental conditions influence the seed moisture content, which, in turn, is related to the percentage of seeds with physical dormancy. There are records of species in which the impermeability is more pronounced when the water content of the seeds is lower. However, there are few references to structural aspects that show the influence of these aspects on the presence or absence of physical dormancy depending on the water content. Therefore, the objectives of the present work are: to characterize, in detail, the testa layers of Leguminosae species, investigating the chemical nature of the cell walls; characterize the ontogenesis of the testa of Erythrina speciosa, with a main focus on the mucilaginous stratum; verify the influence of the environment on physical dormancy before and after dispersal; and evaluate the influence of the seed coat structure on the acquisition of pre- and post-dispersion physical dormancy. The terms macrosclereids and osteosclereids are often misused when they come to seed coats; to avoid the dissemination of incorrect data, the chemical composition of the cell layers that make up the testa must be investigated. The sensu lato cuticle in Leguminosae seeds may not contain lipids in its composition, and, sometimes, the outermost layer of the seed is made up only of pectic compounds; therefore, the term mucilaginous stratum is the most appropriate term to adopt. The mucilaginous stratum is essential for the acquisition and maintenance of physical dormancy in species of Leguminosae, as we have shown experimentally.